2011
DOI: 10.3354/dao02362
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Viral hemorrhagic septicemia virus in the North American Great Lakes region is ­associated with low viral genetic diversity

Abstract: Viral hemorrhagic septicemia virus (VHSV) is a fish rhabdovirus that causes disease in a broad range of marine and freshwater hosts. The known geographic range includes the Northern Atlantic and Pacific Oceans, and recently it has invaded the Great Lakes region of North Ame rica. The goal of this work was to characterize genetic diversity of Great Lakes VHSV isolates at the early stage of this viral emergence by comparing a partial glycoprotein (G) gene sequence (669 nt) of 108 isolates collected from 2003 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
61
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 26 publications
3
61
0
1
Order By: Relevance
“…The simplest hypothesis for this close association of sequence types within an outbreak is that mutations arise during viral replication in a fish and are subsequently introduced and established into other fish associated with the mortality event. Observation of genetic heterogeneity of sequences obtained from single fish as observed in our study and others (Einer-Jensen et al 2004, Thompson et al 2011) support the notion of VHSV quasispecies within a single host. In contrast to the presence of sequence types differing by only 1 or 2 bases, it was also revealed in the dataset presented herein that VHSV outbreaks could be defined by sequence types differing in as much as 24 bases (i.e.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The simplest hypothesis for this close association of sequence types within an outbreak is that mutations arise during viral replication in a fish and are subsequently introduced and established into other fish associated with the mortality event. Observation of genetic heterogeneity of sequences obtained from single fish as observed in our study and others (Einer-Jensen et al 2004, Thompson et al 2011) support the notion of VHSV quasispecies within a single host. In contrast to the presence of sequence types differing by only 1 or 2 bases, it was also revealed in the dataset presented herein that VHSV outbreaks could be defined by sequence types differing in as much as 24 bases (i.e.…”
Section: Discussionsupporting
confidence: 66%
“…However, the VHSV population structure within BC is in contrast to that observed for VHSV emerging in the Great Lakes. Within the BC data set, the ephemeral appearance of 42 sequence types over the 19 yr collection period reveals the occurrence of ongoing sequence divergence and lack of a predominant sequence type, while in the Great Lakes, 2 dominant sequence types accounted for 90% of the isolates collected over a 6 yr period (Thompson et al 2011). The higher abundance of viral variants observed among the BC data set in comparison to the Great Lakes isolates is likely reflective of the temporal differences in viral presence between the 2 regions.…”
Section: Discussionmentioning
confidence: 99%
“…In the other 2 experimental treatments, which were rainbow trout/high injection challenge dose and Pacific herring/low immersion challenge dose, geno- Thompson et al 2011, Ito et al 2012, Pierce & Stepien 2012. Therefore, the observation that genotype IVc caused significantly lower mortality than IVb in the Great Lakes yellow perch provides a preliminary indication that the emergence of genotype IVb may have been associated with an adaptation to higher virulence in yellow perch.…”
Section: Discussionmentioning
confidence: 82%
“…Genotype Ie isolates have been obtained from both the freshwater and the marine environment in Georgia and Turkey (Nishizawa et al 2006). Genotype IV isolates, from North America and Asia (Skall et al 2005), are divided into the sublineages IVa and IVb, of which IVa is primarily restricted to the marine environment in both North America and Asia (Meyers & Winton 1995, Nishizawa et al 2002, Kim et al 2003, Hedrick et al 2003, Lee et al 2007), whereas sublineage IVb isolates have been observed in both freshwater and marine systems in North America only (Gagné et al 2007, Kane-Sutton et al 2010, Thompson et al 2011.…”
Section: Introductionmentioning
confidence: 99%